2017
DOI: 10.1111/bju.13935
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnostic ureteroscopy on intravesical recurrence in patients undergoing radical nephroureterectomy for upper tract urothelial cancer: a systematic review and meta‐analysis

Abstract: Aim of this study was to analyse the association between the use of diagnostic ureteroscopy (URS) and the development of intravesical recurrence (IVR) in patients undergoing radical nephroureterectomy (RNU) for high-risk upper tract urothelial carcinoma. A systematic review of the published data was performed up to December 2016, using multiple search engines to identify eligible studies. A formal meta-analysis was conducted of studies comparing patients who underwent URS before RNU with those who did not. Haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 23 publications
7
88
0
Order By: Relevance
“…Regarding intravesical recurrence, our analysis demonstrated that URS was associated with poorer IRFS (HR = 1.51, 95% CI: 1.29–1.77, P < 0.001) irrespective of prior bladder tumor history (HR = 1.81, 95% CI: 1.53– 2.13, P < 0.001), which is a well‐known prognostic factor of intravesical recurrence [29–32], and was even confined to bladder cuff resection (HR = 1.61, 95% CI: 1.30–1.99, P < 0.001). Similar results were also reported by Marchioni et al . Several theories have been suggested to explain intravesical recurrence after RNU, including intraluminal tumour seeding, intraepithelial cancer migration, and urinary tract cancerisation .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding intravesical recurrence, our analysis demonstrated that URS was associated with poorer IRFS (HR = 1.51, 95% CI: 1.29–1.77, P < 0.001) irrespective of prior bladder tumor history (HR = 1.81, 95% CI: 1.53– 2.13, P < 0.001), which is a well‐known prognostic factor of intravesical recurrence [29–32], and was even confined to bladder cuff resection (HR = 1.61, 95% CI: 1.30–1.99, P < 0.001). Similar results were also reported by Marchioni et al . Several theories have been suggested to explain intravesical recurrence after RNU, including intraluminal tumour seeding, intraepithelial cancer migration, and urinary tract cancerisation .…”
Section: Discussionsupporting
confidence: 91%
“…I n this issue, BJU International has made the conscious decision to publish a systematic review (SR) and metaanalysis (MA) by Guo et al [1] to inform the question of whether patients undergoing nephrouretectomy for upper tract urothelial carcinoma are at increased risk of worse oncological outcomes. This question was also the topic of a similar review by Marchioni et al [2] published earlier this year in this journal. Both studies were submitted around the same time and underwent independent, parallel peer review that resulted in different editorial decisions.…”
mentioning
confidence: 77%
“…This question was also the topic of a similar review by Marchioni et al. published earlier this year in this journal. Both studies were submitted around the same time and underwent independent, parallel peer review that resulted in different editorial decisions.…”
mentioning
confidence: 77%
“…With a pooled analysis of 5 retrospective comparative studies, they underlined a higher hazard of recurrence in those patients undergoing URS. 35 Despite this, we could not assess the use of preoperative URS because it was not routinely used in all the studies included. Another proof of the lower RFS in the SU group was the finding of a statistically significant association of RNU with RFS (HR, 1.26; 95% CI, 1.07-1.49; P ¼ .006).…”
Section: Alessandro Veccia Et Almentioning
confidence: 99%